POTENSI PAJAK DAN RETRIBUSI DAERAH KOTA KENDARI - Hali, Muhammad Syafrudin (JPEP (Jurnal Progres Ekonomi Pembangunan), 2016)
This study aimed at determining and analyzing the growth and contribution of each type of local tax and retribution on the total of local retribution and revenue. It also aimed to analyze the types of local taxes and what local restribution is having potential qualification for development in order to increase local revenue. Result of the study showed that the biggest growth of local revenue is legal miscellaneous local revenue and local tax. The biggest contribution of local revenue is local tax and local retribution. In addition, the biggest contribution of tax on local revenue is restaurant tax and street lights tax, out of eleven types of taxes. The biggest contribution of retribution on local revenue is the retribution of healthcare service by Abunawas hospital and the retribution of building construction permits, out of eight types of retribution. Taxes with potentials qualification are, among others, hotel tax for melati second and restaurant, whereas local retribution with potential for qualification are the retribution of healthcare service by Abunawas hospital and retribution of building contstruction permits. Keywords : Potential Revenue, Tax, And Retribution